Realization of an integrated seeding and compensating potato planter based on one-way clutch - Wang, Guanping; Sun, Wei; Chen, Lea-Der; Zhang, Hua; Liu, Xiaolong; Li, Hongling; Yang, Xiaoping; Yang, Hao (International Journal of Agricultural and Biological Engineering, 2020)
The yield reduction caused by miss-seeding in potato mechanized sowing is astonishing. The existing research always needs to install a spare compensator on the original seed-metering device. Therefore, problems of complex planter structure and compensated potato seed poor landing accuracy need to be solved urgently. Consequently, a scheme of integrated seeding and compensating potato planter based on one-way clutch is proposed in this paper. Based on a basic ‘improved one raw potato planter’ and the working principle of one-way clutch, power of seed-metering system is provided through main power transmission one-way clutch by land wheels when the system works properly. However, when miss-seeding detection system with infrared radiation deciding that a miss-seeding incident has happened, the seed-metering power will be replaced by a compensatory motor through compensating one-way clutch at a higher speed. Thus, the idea of catching-up compensation can be realized. After compensation is completed, the system controller disconnects the compensatory motor, and the seed-metering power will naturally switch to the land wheels again. A prototype based on this idea was built. Field tests showed that the accuracy of seed monitoring system is more than 99.9%; the adoption of catching-up compensation scheme does not bring about empty spoon rate rise significantly. Within the range of 0.2-0.8 m/s of the seed-metering chain speed, although the average success compensation rate decreases evidently with the increase of the chain speed, the success compensation rate is still near 70% even at 0.8 m/s, the vast majority of missed seeds can be compensated effectively.Keywords: potato planter, infrared radiation miss-seeding detection, one-way clutch, catching-up compensationDOI: 10.25165/j.ijabe.20201303.5450Citation: Wang G P, Sun W, Chen L D, Zhang H, Liu X L, Li H L, et al. Realization of an integrated seeding and compensating potato planter based on one-way clutch. Int J Agric & Biol Eng, 2020; 13(3): 79–87.